Updating inflation expectations - Michael J. Lamla; Samad Sarferaz (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper investigates how inflation expectations evolve. In particular, we analyze the time-varying nature of the propensity to update expectations and its potential determinants. For this purpose we set up a flexible econometric model that tracks the formation of inflation expectations of consumers at each moment in time. We show that the propensity to update inflation expectations changes substantially over time and is related to the quantity and the quality of news.
Keywords: E31; E37; E52; D83; 330; inflation expectation formation; time-varying parameters; Bayesian methods; disagreement; media coverage; stochastic volatility; Inflationserwartung; Zeit; Informationsverhalten; Wirtschaftsinformation; Schätzung; Deutschland